2017
DOI: 10.1111/irfi.12161
|View full text |Cite
|
Sign up to set email alerts
|

Technical Analysis Profitability Without Data Snooping Bias: Evidence from Chinese Stock Market

Abstract: We perform a comprehensive analysis on the profitability of a large number of technical analysis based trading rules in Chinese stock market. To counter data snooping bias, we employ a stepwise superior predictive ability test to identify genuinely profitable trading rules among more than 28,000 technical signals. Using 19 years of daily data on Chinese aggregate stock market return, we find substantial evidence on the profitability of technical trading rules measured by either the market timing ability or Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Similar empirical evidence was also provided by Marshall et al (2017). Next, Jiang et al (2017) found robust and substantial evidence of the profitability of TRs for the Chinese stock market. M'ng (2018) devised a novel adjustable moving average indicator for the Far East equity markets that resulted in excess returns over the buy-and-hold strategy.…”
Section: Introductionsupporting
confidence: 72%
“…Similar empirical evidence was also provided by Marshall et al (2017). Next, Jiang et al (2017) found robust and substantial evidence of the profitability of TRs for the Chinese stock market. M'ng (2018) devised a novel adjustable moving average indicator for the Far East equity markets that resulted in excess returns over the buy-and-hold strategy.…”
Section: Introductionsupporting
confidence: 72%
“…Empirical evidence shows that according to the technical analysis, the proposed pattern-based approach can get excess returns and beat buy-and-hold strategies. In addition, recent studies have shown that technical analysis indicators can obtain excess returns compared to the broader market in investment trading strategies [38], [39], [40], [41], [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors reported evidence of profitability for rules based on classical moving average as well as rules based on Bollinger bands and relative strength index. Jiang, Tong & Song (2019) investigated the profitability of trading rules in Chinese stock market. The authors used 19 years daily data from Chinese aggregate market return and confirmed the profitability of trading rules even in the presence of transaction costs.…”
Section: Literature Reviewmentioning
confidence: 99%